Merging Scientific Knowledge and Operational Experience: Lessons Learnt in Applying a Fatigue Risk Management System to Ultra Long Range Operations - Signal TL; van den Berg M; Ladyman C; Zaslona J; Hughes M; Johnston B; Dyer C; Glover M (Thieme Revinter Publicações Ltda on behalf of the Brazilian Sleep Academy, 2025)
Introduction: Fatigue Risk Management Systems (FRMSs) are utilized in the aviation industry to manage the fatigue risks associated with Ultra Long Range (ULR) operations. In these operations, fatigue risks are primarily created by very long flight and duty times which result in prolonged periods of wake and limited opportunities for sleep, operating the aircraft during the circadian nadir, and circadian disruption associated with large time zone changes. A key aspect of FRMSs is the combined use of scientific and operational knowledge to identify and manage fatigue risks. The integration of knowledge is described here in relation to the planning and operation of two ULR routes (Auckland-Chicago-Auckland and Auckland-New York-Auckland). Methods: ULR operations in this airline are embedded within the wider safety and risk management processes, which include an existing FRMS that apply to all flight operations. Before beginning each ULR operation, a safety case was developed by the airline that included identification of risks, proposed mitigations and biomathematical model predictions of fatigue at key points in each flight. Prior to submission to the regulator for approval, the safety case received independent scientific review. A condition of regulatory approval to operate the route and part of special scheduling agreements between the airline and the pilot body was data collection during initial operations to determine if fatigue mitigations were functioning as intended. Results: Three studies were conducted, the first for the initial Auckland-Chicago operation, the second after altering the crew complement on this route (from 2 Captains and 2 First Officers to 1 Captain, 2 First Officers, 1 Second Officer) and the third at the commencement of the Auckland-New York route. Each study was designed with input from scientists, operational personnel and pilot union representatives, and utilized valid and reliable measures of fatigue, sleepiness, sleep, and performance. Data from each study were analyzed and reported independently by fatigue scientists but a collaborative approach was used in the application of findings to produce recommendations of operational value. For example, findings from the first study were used to educate pilots and enhance the guidance provided on in-flight rest and inform the in-flight rest pattern for the second ULR route. Conclusion: This example demonstrates the importance and value of combining expertise in fatigue science and safety science with operational knowledge to manage fatigue risk in safety critical operations. It also supports the need for a tripartite approach in conjunction with fatigue education to get buy-in from crew to participate in these studies and engage in the recommendations that emerge from them. Support: Funding for the three studies was provided by the airline.